The State of Play of CSR in Singapore - Tan, Eugene K B (Institutional Knowledge at Singapore Management University, 2011)
Given Singapore’s status as an economic powerhouse in the Asian region, it might be reasonable to assume that the level of Corporate Social Responsibility (CSR) activity would be proportionate. However, in frequent comparisons of CSR across countries, both academically and anecdotally, Singapore seems to fall short. The understanding of CSR has not kept pace with the expectations and demands placed on business by the various stakeholders, including consumers and governments. It would be worthwhile to understand the reasons why this is so. The research has three objectives: - To examine the drivers of and impediments to CSR in Singapore; - To explore whether CSR is important for the future development of Singapore based enterprises, and Singapore generally; and - To propose how CSR can be made more relevant in the Singaporean context. Through exploring these questions, we hope to arrive at a more holistic understanding of how CSR is animated in Singapore, apart from purely economic motivations. And perhaps, we will be better able to account for the current ambivalence towards CSR that is prevalent in the private sector.